A H2S Donor GYY4137 Exacerbates Cisplatin-Induced Nephrotoxicity in Mice - Mi Liu; Zhanjun Jia; Ying Sun; Aihua Zhang; Tianxin Yang (Mediators of Inflammation)
Accumulating evidence demonstrated that hydrogen sulfide (H2S) is highly involved in inflammation, oxidative stress, and apoptosis and contributes to the pathogenesis of kidney diseases. However, the role of H2S in cisplatin nephrotoxicity is still debatable. Here we investigated the effect of GYY4137, a novel slow-releasing H2S donor, on cisplatin nephrotoxicity in mice. Male C57BL/6 mice were pretreated with GYY4137 for 72 h prior to cisplatin injection. After cisplatin treatment for 72 h, mice developed obvious renal dysfunction and kidney injury as evidenced by elevated blood urea nitrogen (BUN) and histological damage. Consistently, these mice also showed increased proinflammatory cytokines such as TNF-α, IL-6, and IL-1β in circulation and/or kidney tissues. Meanwhile, circulating thiobarbituric aid-reactive substances (TBARS) and renal apoptotic indices including caspase-3, Bak, and Bax were all elevated. However, application of GYY4137 further aggravated renal dysfunction and kidney structural injury in line with promoted inflammation, oxidative stress, and apoptotic response following cisplatin treatment. Taken together, our results suggested that GYY4137 exacerbated cisplatin-induced nephrotoxicity in mice possibly through promoting inflammation, oxidative stress, and apoptotic response.